2021
DOI: 10.1038/s41598-021-86146-w
|View full text |Cite|
|
Sign up to set email alerts
|

Astaxanthin protects against early acute kidney injury in severely burned rats by inactivating the TLR4/MyD88/NF-κB axis and upregulating heme oxygenase-1

Abstract: Early acute kidney injury (AKI) contributes to severe morbidity and mortality in critically burned patients. Renal inflammation plays a vital role in the progression of early AKI, acting as a therapeutic target. Astaxanthin (ATX) is a strong antioxidant widely distributed in marine organisms that exerts many biological effects in trauma and disease. ATX is also suggested to have anti-inflammatory activity. Hence, we attempted to explore the role of ATX in protecting against early postburn AKI via its anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Suzuki et al demonstrated that AST has a dose-dependent ocular anti-inflammatory effect through suppression of NO, TNF-α, and prostaglandin E2 (PGE2) production, which occurs by blocking the NF-κB transcription factor [105]. Similarly, another study demonstrated that AST reduced renal inflammation in a dose-related manner by regulating the NF-κB pathway and HO-1, ultimately preventing acute kidney injury [106]. Other authors have reported that AST inhibited NF-κB and Wnt/β-catenin signaling pathways in hepatocellular carcinoma cells and in a hamster model of oral cancer [103,107].…”
Section: Astaxanthin and The Crosstalk Between Nf-κb And Nrf2mentioning
confidence: 99%
“…Suzuki et al demonstrated that AST has a dose-dependent ocular anti-inflammatory effect through suppression of NO, TNF-α, and prostaglandin E2 (PGE2) production, which occurs by blocking the NF-κB transcription factor [105]. Similarly, another study demonstrated that AST reduced renal inflammation in a dose-related manner by regulating the NF-κB pathway and HO-1, ultimately preventing acute kidney injury [106]. Other authors have reported that AST inhibited NF-κB and Wnt/β-catenin signaling pathways in hepatocellular carcinoma cells and in a hamster model of oral cancer [103,107].…”
Section: Astaxanthin and The Crosstalk Between Nf-κb And Nrf2mentioning
confidence: 99%
“…However, the important thing that gets overlooked is that tolllike receptor 4 (TLR4), as one of the important receptors for inflammation recognition, activates the myeloid differentiation factor 88 (MyD88)-dependent pathway, which in turn activates nuclear factor kappa B (NF-kB), and ultimately leads to the release of inflammatory mediators and cytokines, thus playing an antiinflammatory immunomodulatory role (20,21). A growing number of studies have shown that the TLR4/MyD88/NF-kB signaling pathways play a key role in the pathogenesis and treatment of a variety of diseases (22)(23)(24). The innate immune response induces an inflammatory response, which is primarily mediated by cytokines, and the crucial pro-inflammatory cytokines, such as tumor necrosis factor a (TNF-a) and interleukin 8 (IL-8), possess the capabilities of increasing the synthesis of small inflammatory mediators and initiating inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…Another paper demonstrated that ATX liposomes attenuated LPS-induced acute liver injury in rats, reporting a higher antioxidant and anti-inflammatory activity than free ATX due to an enhancement of its oral bioavailability [230]. In the same line, treatment with ATX (5, 10 and 20 mg/kg) dose-dependently protected against burn-induced acute kidney inflammation through suppression of the TLR4/NF-κB pathway and an increase in HO-1 levels [231].…”
Section: In Vivo Studiesmentioning
confidence: 94%